Straussophobia : defending Leo Strauss and Straussians against Shadia Drury and other accusers - Minowitz, Peter, 1955- (Lexington Books, 2009)
Leo Strauss and his students have long been accused of mendacity, elitism, and militarism, but the Iraq War has prompted unprecedented levels of caustic and inaccurate denunciations. Inappropriate criticisms have issued from artists (Tim Robbins), politicians (Ron Paul), journalists (Joe Klein), and even highly lauded scholars such as Arthur Schlesinger, Jr., Gordon Wood, Douglas Massey, Stephen Holmes, Anne Norton, Shadia Drury, Sheldon Wolin, John Pocock, John Yolton, Nicholas Xenos, and Brian Leiter. In Straussophobia, Peter Minowitz provides a methodical and detailed critique of the major o.